Andreas Vesalius as a renaissance innovative neuroanatomist: his 5th centenary of birth - Marleide da Mota Gomes; Mauricio Moscovici; Eliasz Engelhardt (Arquivos de Neuro-Psiquiatria)
Andreas Vesalius (1514-1564) is considered the Father of Modern Anatomy, and an authentic representative of the Renaissance. His studies, founded on dissection of human bodies, differed from Galeno, who based his work on dissection of animals, constituted a notable scientific advance. Putting together science and art, Vesalius associated himself to artists of the Renaissance, and valued the images of the human body in his superb work De Humani Corporis Fabrica.This paper aims to honor this extraordinary European Renaissance physician and anatomist, who used aesthetic appeal to bind text and illustration, science and art. His achievements are highlighted, with an especial attention on neuroanatomy. Aspects about his personal life and career are also focused.